Role of Chrononutrition in Modulating Metabolic and Cardiovascular Health - Shukla, Vani; Hussain, Sahil; Fatima, Ghizal; Khan, Sadaf; Hadi, Najah; Fedacko, Jan; Magomedova, Aminat (Scripta Medica, 2026)
Maintaining optimal cardiovascular and metabolic health depends on aligning dietary practices with the body’s intrinsic circadian rhythms. Chrononutrition is a rapidly advancing research area that explores how the timing of food intake influences physiological health outcomes. Unlike conventional nutritional strategies that emphasise food quantity and composition, chrononutrition highlights meal timing as a critical regulator of metabolic processes, including glucose metabolism, insulin responsiveness and lipid regulation. Accumulating evidence indicates that unfavourable eating behaviours, particularly late-day or nighttime food consumption, are closely associated with metabolic impairments and an increased risk of conditions such as obesity, type 2 diabetes and cardiovascular disease. By integrating principles of nutrition with chronobiology, chrononutrition offers a promising approach for reducing the burden of chronic diseases. This review evaluates the role of chrononutrition in metabolic and cardiovascular health, with particular emphasis on time-restricted eating (TRF), consistency in meal timing and the underlying molecular mechanisms responsible for the observed health benefits. Overall, the findings suggest that dietary strategies synchronised with biological clocks may represent an effective approach for chronic disease prevention.